THE INFLUENCE OF PARENTAL ATTACHMENT AND PEER INTERACTION ON THE AGGRESSIVE BEHAVIOR OF ADOLESCENTS IN BOGOR - Purnama, Nurjanah; Pramudita, Aisyah; Wiratmaja, Laura Virgita; Riany, Yulina Eva (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
The environment, including family and peer interactions, can influence the level of aggressiveness in adolescents. This quantitative study aims to analyze the influence of parental attachment and peer interaction on adolescent aggressive behavior in Bogor. The study involved 115 respondents from grade 10 at the Bina Bangsa Sejahtera Islamic High School, consisting of 68 male students (59%) and 47 female students (41%), aged between 13-18 years. Data were collected using questionnaires and analyzed using statistical correlation and multiple regression tests with SPSS 26. The results show that secure parental attachment is associated with lower adolescent aggression, while insecure attachment positively correlates with higher aggression. Peer interaction, including relationships and bonds with friends, and variables like school conditions, significantly impact adolescent aggressive behavior. These findings indicate that parental and school roles can help prevent aggressive behavior in adolescents. Therefore, it is essential to educate parents, teachers, and adolescents on maintaining healthy parental relationships, fostering positive peer interactions, and understanding the dangers of aggressive behavior. Government involvement is also needed to support the development of such programs.